Treatment of aortoesophageal fistula after endovascular aortic repair for mycotic thoracic aneurysm secondary to endoscopic botulinum toxin injections - Michaël Huysmans; Jürgen Verbist; Wouter Van den Eynde; Fien Gryffroy; Koen Vermeiren; Pieter-Jan Cuyle (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Endoscopic botulinum toxin injections to the esophagus is a safe and effective treatment for the management of achalasia or distal esophageal spasms. This case study describes a complication of late mycotic aneurysm formation at the level of the descending thoracic aorta requiring urgent endovascular repair. Afterwards, development of an aortoesophageal fistula demanded radical surgical therapy consisting of esophageal resection, stent-graft removal and both aortic and esophageal reconstruction.